A phase III, randomized, non-inferiority study comparing the efficacy and safety of biosimilar filgrastim versus originator filgrastim for chemotherapy-induced neutropenia in breast cancer patients (Clinics, 2016)
OBJECTIVES: To compare the efficacy and safety of two filgrastim formulations for controlling chemotherapy-induced neutropenia and to evaluate the non-inferiority of the test drug relative to the originator. METHODS: This phase III non-inferiority study had a randomized, multicenter, and open-label design. The patients were randomized at a ratio of 1:1 with a follow-up period of 6 weeks for each patient. In both study arms, filgrastim was administered subcutaneously at a daily dose of 5 mg/kg body weight. The primary endpoint was the rate of grade 4 neutropenia in the first treatment cycle. The secondary endpoints were the duration of grade 4 neutropenia, the generation of anti-filgrastim antibodies, and the rates of adverse events, laboratory abnormalities, febrile neutropenia, and neutropenia of any grade. RESULTS: The primary efficacy analysis demonstrated the non-inferiority of the test drug compared with the originator drug; the upper limit of the 90% confidence interval (CI) for the rate of neutropenia between the two groups (12.61%) was lower than the established margin of non-inferiority. The two treatments were similar with respect to the secondary endpoints and safety. CONCLUSION: The efficacy and safety profile of the test drug were similar to those of the originator product based on the rate of grade 4 neutropenia in the first treatment cycle. This study supports Anvisa’s approval of the first biosimilar drug manufactured by the Brazilian industry (Fiprima¯).